Determination of Phenolic Compounds in Litchi Juices by Solid-Phase Extraction and High Performance Liquid Chromatography - Wu, M.; Hu, Z.Y.; Zheng, P.; Zhang, L. (Asian Journal of Chemistry, 2013)
A simple analytical method for the quantitative determination of phenolic compounds in litchi juice was developed. The phenolic compounds in litchi juice were extracted by solid-phase extraction using Bound Elut C18 cartridges and the extract was analyzed by HPLC coupled with UV detection. Solid-phase extraction conditions were as follows: samples were adjusted to pH 3.0, cartridges firstly were washed by 5 mL 0.01 M HCl then 5 mL distilled water, at last phenolic compounds on C18 cartridge were eluted by 7 mL methanol. Elution were blowed to 1 mL by pressure blowing concentrator. Phenolic compounds separation effect was good and extraction rate was high in this solid-phase extraction procedure. This paper gave a method to extract and determine fastly phenolic compounds present in Litchi juice.